2009
DOI: 10.1002/pen.21363
|View full text |Cite
|
Sign up to set email alerts
|

Sol‐gel process of alkyltriethoxysilane in latex for alkylated silica formation in natural rubber

Abstract: Sol‐gel process of alkyltriethoxysilanes that was dispersed in natural rubber latex was used to generate alkylated silica particles inside the rubber matrix. Three types of alkyltriethoxysilanes were chosen, i.e., vinyltriethoxysilane (VTOS), ethyltriethoxysilane (ETOS), and i‐butyltriethoxysilane (BTOS), as they differed in the type of one substituent group. Together with tetraethoxysilane (TEOS), a typical precursor for silica formation, all silanes were studied for their conversion to silica and subsequent … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
19
0

Year Published

2014
2014
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 23 publications
(19 citation statements)
references
References 19 publications
0
19
0
Order By: Relevance
“…Several reports are available in the literature on the in situ generation of silica in the different rubber matrices such as natural rubber (NR), isoprene rubber (IR), styrene butadiene rubber (SBR), polydimethylsiloxane (PDMS), ethylene propylene diene monomer rubber (EPDM), butadiene rubber (BR), acrylic rubber (ACM), and chloroprene rubber (CR) . However, research on nitrile rubber (NBR) filled with in situ silica is very limited.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Several reports are available in the literature on the in situ generation of silica in the different rubber matrices such as natural rubber (NR), isoprene rubber (IR), styrene butadiene rubber (SBR), polydimethylsiloxane (PDMS), ethylene propylene diene monomer rubber (EPDM), butadiene rubber (BR), acrylic rubber (ACM), and chloroprene rubber (CR) . However, research on nitrile rubber (NBR) filled with in situ silica is very limited.…”
Section: Introductionmentioning
confidence: 99%
“…In the solution method, dissolution of rubber in a proper solvent, followed by the addition of TEOS, water, and catalyst to the rubber solution is carried out. 12 Several reports are available in the literature on the in situ generation of silica in the different rubber matrices such as natural rubber (NR), [13][14][15][16][17][18][19] isoprene rubber (IR), [20][21][22] styrene butadiene rubber (SBR), [23][24][25][26] polydimethylsiloxane (PDMS), 27,28 ethylene propylene diene monomer rubber (EPDM), [29][30][31] butadiene rubber (BR), 11 acrylic rubber (ACM), 32 and chloroprene rubber (CR). 33 However, research on nitrile rubber (NBR) filled with in situ silica is very limited.…”
Section: Introductionmentioning
confidence: 99%
“…To solve this problem, the use of different silane coupling agents to improve rubber–filler interaction has been reported . An alternative and interesting method for overcoming the abovementioned difficulties is the application of in situ generation of an inorganic oxide (silica, alumina, titania, and others) in the rubber matrix by means of a sol–gel process.…”
Section: Introductionmentioning
confidence: 99%
“…Excellent tensile properties were observed when the in situ silica content was increased. As well as SBR latex, NBR latex and NR latex were investigated. However, no study revealed the actual morphological characteristic features of in situ silica generated in the latexes because the precipitation technique followed by two‐roll milling was used, which can affect the in situ silica morphology.…”
Section: Filler Network Formation By In Situ Silica Filling In Naturamentioning
confidence: 99%